(3GdEUdGMs - (3GdWHGWHGFj GdcQHdGFj, GdeLGgO, eMeO Hf Ydj Hf eMeO Hf Ydj, J (B1242 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj egO dfG WQjb EUdGM GdYed CeG HYO ajbhd eMeO Hf Ydj GdWHGWHGFj gPG cJGH LeYJ ajg eSGFd GdMdGd hGdMQGe hChOYJ ajg GdSff hGdCMcGe hSejJg HGdEUdGM s
(3BNQgG (B:s
(3de CLO CMOG UQM HCMO GdCeQjf hGdCbQH YfOj gh GdGMJeGd GdKGfj eY Cfg CMhW hEPG cGf Gdehdi UZjQG acG cRhL GdUZjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3 / 3/543s
(3gOjI GdYGQajf (B2 / 263s
(3GdPQjYI (B2 / 170s
(3EjVGM Gdecfhf (B1 / 91s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis